AN ANALYSIS METAPHOR IN SELECTED SONG BY JAMES ARTHUR - Dwi Ayu, Ningrum; Wibowo, Hanafi (Teaching English as Foreign Language, Literature and Linguisticss, 2024)
This research analyses the expression of metaphors in the Selected James Arthur's song In this research, the author analyzes the types of metaphors that are used based on Lakoff & Johnson's theory in James Arthur's song lyrics. By using the qualitative method, Metaphor is the most used figurative language to express sadness in James Arthur's song lyrics. Based on the analysis of 25 metaphors, it was found that conceptual metaphor was the most dominant type, with a frequency of 10 times (40%). Conceptual metaphors describe the relationship between one idea and another more concrete idea, such as describing life as a journey. This type helps the listener or reader understand abstract concepts in a more familiar and digestible way. Ontological metaphors took second place with a frequency of 9 times (36%). This type transforms an abstract or formless experience into something more concrete, such as emotions described as objects that can be touched or moved. The use of this metaphor often makes it easier for someone to visualize complex ideas. Meanwhile, orientational metaphors appeared 6 times (24%). Overall, these results suggest that conceptual metaphors are more widely used, perhaps due to their flexibility in conveying abstract ideas, whereas ontological and orientational metaphors complement the narrative more concretely and emotionally